Two new bat species for Vietnam - Thong, Vu Dinh; Huynh, Dang Huy; Khoi, Le Vu (Academia Journal of Biology, 2014)
This paper basically describes two bat species new to Vietnam, Myotis formosus (Hodgson, 1835) and Eptesicus serotinus (Schreber, 1774) These species belong to the family Vespertilionidae. Myotis formosus is a medium-sized Myotis species with forearm length: 44.0-49.5 mm; tail length: 35.8-48.5 mm; hindfoot length: 10.0-11.8 mm; tibia length: 21.0-23.5 mm; ear length: 12.5-14.8 mm. Pelage is distinct with yellow brown or dark brown on the dorsal surface and dark orange on the ventral surface. Ear is relatively short with darker margin. Anti-tragus is long, narrow and relatively pointed with straight anterior edge and convex posterior one. This species has been recorded from Afghanistan, China (Taiwan), Korea, Japan, Philippines, Indonesia, and Nepal. In Vietnam, it was recorded from two national parks: Cucphuong and Xuanson. Eptesicus serotinus is characterised by a long tail with the tip exceeds the tail membrane about 5.0 mm. Ears are long and broad with the straight anterior edge and the convex posterior one. Base of the posterior edge is strongly notched. The fifth finger is shorter than the fourth and the third ones. The wing membrane is attached to the base of the outer toe. Dorsal surface of the tail membrane is covered by dark brown or light black hairs. Forearm length: 44.0-56.5 mm; m1 and m2 are of equal size; length of c-m3: 7.0-8.5 mm. It is noticeable that the skull of the species is relatively flat. This species has been recorded from India, Pakistan, Nepal and Afghanistan. In Vietnam, this species was only recorded from the Xuanson national park.